Combining neoadjuvant chemotherapy with PD-1/PD-L1 inhibitors for locally advanced, resectable gastric or gastroesophageal junction adenocarcinoma: A systematic review and meta-analysis - Yuan, Zhen; Cui, Hao; Wang, Shuyuan; Liang, Wenquan; Cao, Bo; Song, Liqiang; Liu, Guibin; Huang, Jun; Chen, Lin; Wei, Bo (Frontiers in Oncology, 2023)
Background: Immune checkpoint inhibitors (ICIs) have shown promising prospects in locally advanced, resectable gastric or gastroesophageal junction adenocarcinoma (GC/GEJC) immunotherapy, but their efficacy in neoadjuvant settings remains unclear. This study aimed to assess the efficacy and safety of integrating PD-1/PD-L1 inhibitors into neoadjuvant chemotherapy (NACT) of GC/GEJC treatment. Methods: The PubMed, Cochrane Library, Embase, ClinicalTrials.gov, and main oncology conferences databases were systematically searched up to 11/19/2022, and randomized controlled trials (RCTs) and cohort studies that evaluated the efficacy and safety of PD-1/PD-L1 inhibitors plus NACT were included. The main outcomes were pathological complete response (pCR), major pathological response (MPR), R0 resection rate, and treatment-related adverse events (TRAEs). Results: A total of 753 patients from 20 prospective studies were included in this meta-analysis. The pooled pCR and MPR rates from studies reporting were 21.7% (95% CI, 18.1%-25.5%) and 44.0% (95% CI, 34.1%-53.8%), respectively. The pooled incidence of total TRAEs was 89.1% (95% CI, 82.7%-94.3%), and the incidence of grade 3-4 TRAEs was 34.4% (95% CI, 17.8%-66.5%). The pooled R0 resection rate was reported to be 98.9% (95% CI, 97.0%-99.9%). Subgroup analysis have not found significant differences in efficacy and safety among different PD-1/PD-L1 inhibitors. Moreover, the efficacy in patients with positive PD-L1 expression [combined positive score (CPS) ≥1] was comparable to that in the entire study population [pCR, 22.5% vs. 21.2% (p > 0.05); MPR, 48.6% vs. 43.7% (p > 0.05)]. Conclusion: This systematic review and meta-analysis found that PD-1/PD-L1 inhibitors combined with NACT for locally advanced GC/GEJC were well tolerated and may confer therapeutic advantages. The integration of ICIs into NACT has shown the potential for application in any PD-L1 expression population.